Peran Cytidine 5'-diphosphocoline dalam Penatalaksanaan Nyeri Neuropatik - Dessy R Emril (Jurnal Kedokteran Syiah Kuala, 2010)
Abstrak.  Riview terhadap mekanisme nyeri neuropatik ini adaJah berdasarkan respon yang sangat kompleks terhadap injuri saraf perifer. Terdapat berbagai kemungkinan mekanise yang mendasari terjadinya nyeri neuropatik  tennasuk keterlibatan saraf perifer, medulla spinalis,  bahkan otak. Penelitian selanjutnya  terhadap mekanisme nyeri neuropatik akan membantu kita dalam mengembangkan obat-obat baru yang bekerja pada target tertentu berdasarkan mekanisme yang terjadi. Sehingga prinsip pengobatan yang bersifat simtomatik akan berubah menjadi pengobatan yang bedasarkan mekanisme atau patobiologinya. Dengan dasar pemikiran tersebut saat ini kita sedang    mencoba    mengembangkan    tentang    peran    Cytidine    5 '-dipbosphocoline    dalam penatalaksanaan nyeri neuropatik._(JKS2010; 1:51-62)Kata   kunci:   nyeri  neuropatik,  mekanisme  nyeri  neuropatik, penatalaksanaan,  Cytidine  5 '- diphosphocolineAbstract.   This brief overview of the known mechanisms of neuropathic pain outlines the complex nature of the responses to a peripheral nerve injury. A unifying hypothesis of a single  mechanism of all  neuropathic pain  is most unlikely to be proven and it is  probable that an inter-related portfolio of mechanisms contribute to the generation  of neuropathic pain in any given  patient, with peripheral,  spinal and brain events possibly  all playing a role.  Further elucidation  of mechanisms underlying neuropathy will assist  in developing novel targets for drug therapy.  It may be possible to improve the ethos of clinical  management protocols so that there will be a move away from the current disease based treatment towards symptom or, ultimately, mechanism based therapies.  It  is a clinical challenge to determine which mechanisms may be operating and hence responsible for individual symptomology in each patient. Mechanism based therapy will require a better understanding of mechanisms involved  in neuropathic pain and reliable convenient tools for their assessment in the clinic.  According to the established  mechanisms, we are trying to elaborate  the role ofCytidine  5'-diphosphocoline  for the treatment ofneuropathic pain.  (JKS 2010; 1:51-62)Keywords:    neuropathic  pain,   NP   mechanism,   mechanisms  based  treatment,  Cytidine   5'- diphosphocoline